(untitled) (Bulletin KNOB, 2014)
The Regional Archives ‘Hollands Midden’ has a fairly complete file on the Van Beverningh Chapel, a monumental burial chapel on the south side of the choir aisle of the St Jans Church in Gouda. The file includes a large number of letters, invoices, quotes and specifications regarding the purchase, construction and maintenance of the burial chapel. The client, Gouda citizen Hieronymus Van Beverningh (1614-1690), held important posts in the municipal government of Gouda and became member of the Staten-Generaal (a forerunner of the Dutch parliament) in 1653. In 1655, he married Johanna le Gillon (1635-1706), who came from an influential Amsterdam family. The Van Beverninghs moved in the highest circles of the Republic. In Gouda, Van Beverningh maintained close ties with the municipal government and with the powerful Van der Dussen family. His nephew Jacob van der Dussen held the positions of sheriff, treasurer and mayor several times there. Van Beverningh was also a friend of Johan de Witt and he and his wife maintained friendly relations with Constantijn Huygens. He became one of the most important diplomats for the Republic and successfully undertook many peace missions. The portraits of him and his wife, painted by Jan de Baen in 1670, reflect the standing of the Van Beverninghs. Van Beverningh was portrayed with the Treaty of Aachen of 1668, in the Minisigning of which he had played an important role. The painting also shows vast gardens, a reference to his passion for botany and gardening. The burial chapel in the St-Jans Church was to do justice to the status that Van Beverningh had achieved in his career. With its impressive marble front and carvings, the Chapel is second to none of the other important monuments of the period. Van Beverningh contracted a number of prominent masters and had the chapel built entirely from Carrara marble. The chapel’s facade may well have been designed by Pieter Post. The carvings must have been commissioned already well before August 1668 and their actual realization can be ascribed with certainty to Bartholomeus Eggers. Both these men were working on the Waag in Gouda in that same period. The carvings for the interior were probably designed by Artus Quellinus, but no documents of this have survived. The stone carver Jacob Roman was involved in their realization and local craftsmen that were hired were also involved in other important building projects in Gouda. The transport of the marble blocks – for which warships were deployed – from Carrara to Gouda proved to be a troublesome affair. Van Beverningh went to great lengths to bring the marble to Gouda, which testifies to the great ambitions he had for the chapel.